A comparison of attitudes to laryngeal cancer treatment outcomes: A time trade‐off study. (11th July 2017) - Hamilton, D.W.; Pedersen, A.; Blanchford, H.; Bins, J.E.; McMeekin, P.; Thomson, R.; Paleri, V.; Wilson, J.A.
Abstract : Design: Time trade‐off choice experiment. Setting: Two large head and neck cancer centres. Participants: Patients who have received treatment for head and neck cancer and members of the head and neck cancer multidisciplinary team. Main outcome measures: Participants were asked to rank the outcome scenarios, assign utility values using time trade‐off and rate the importance of survival on treatment choice. Results: A total of 49 patients with head and neck cancer and 73 staff members were recruited. Chemoradiotherapy (CRT) optimal outcome was the most preferred health state (34 of 49, 69% patients, and 50 of 73, 68% staff), and CRT with complications was least preferred (27 of 49, 55% patients, and 51 of 73, 70% staff). Using time trade‐off, mean utility values were calculated for CRT optimal outcome (0.73 for patients, 0.77 for staff), total laryngectomy (TL) optimal outcome (0.67 for patients, 0.69 for staff), TL outcome with complications (0.46 for patients, 0.51 for staff) and CRT with complications (0.36 for patients, 0.49 for staff). The average survival advantage required for a participant to change their preferred choice was 2.6 years. Conclusions: We have demonstrated that a significant proportion of patients with head and neck cancer and staff members would not choose CRT to manage locally advanced laryngeal cancer. Staff members rated the health states associated with laryngeal cancer treatment higher than patients who have experienced them, and this is particularly evident when considering the poorer outcomes. The head and neck cancer community should develop methods of practice and decision‐making which incorporate elicitation and reporting of patient values as a central principle.